SDG's and Zero Emission Vision in Indonesia: Implementation of Green Marketing and 'Green' Direct Marketing Campaign Opportunities based on Population Database - Taufiq Rahmat; Ratih Hurriyati; Puspo Dewi Dirgantari (UIN Sunan Gunung Djati Bandung, 2022)
This study was conducted in Indonesia to achieve Zero Emissions and SDG'S by increasing public awareness as consumers of big data-based direct marketing campaign opportunities with a Green Marketing approach. Researchers used qualitative research methods with a descriptive design. The data collection technique was carried out in a triangulation (combined) manner, and the data analysis was inductive. The data source used in this research is secondary data with documentation from reputable scientific journals, official news, and reports. Data analysis in this study used Miles and Huberman's interactive data analysis model, namely data reduction, data presentation, and conclusion drawing/verification. The observations show that the trend of green marketing in Indonesia has been implemented, both from the production side (corporations) and the consumption side (consumers). However, the results are still far from the zero-emission target. Marketers' understanding and knowledge indicate that consumers' green consumption behavior should focus on increasing appropriate communication about the benefits of green consumption among consumers. It is characterized by the Achievement of Household Waste Management Performance which is the most significant contribution showing that green consumer behavior is still low. Through green communication and promotions, marketers and policymakers will be able to emphasize the benefits of practicing GCB among consumers. Normatively, the government can supervise products that claim to be environmentally friendly in the spirit of achieving sustainable production and consumption activities. In addition, the government can make Population Data linked to cellphone SIM card numbers and connected to other social media applications to become databases in implementing green marketing in the sense of building green consumer behavior through green campaigns.